Risk factors for shoulder injury in professional male handball players: A systematic review - Damjan Jakšić; Stefan Maričić; Mila Vukadinović Jurišić; Marijana Čavala (University of Novi Sad, Faculty of Sport and Physical Education, 2024)
Handball is a globally popular and physically demanding sport that requires high-intensity intermittent activities, with a particular emphasis on frequent ball throwing or shooting. The primary aim of this systematic review was to identify the risk factors for shoulder injuries in professional male handball players. The secondary aim is to propose preventive measures for reducing shoulder injuries in professional or elite handball players. This study followed the guidelines provided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Web of Science, PubMed, Science Direct, and Google Scholar were used to identify relevant studies. Only 8 studies met the eligibility requirements and were incorporated into the review. The Physiotherapy Evidence Database (PEDro) was assessed for the methodological quality of studies. Seven of the total eight studies were considered moderate quality, however, only one study was considered low quality. Based on this review findings, the following risk factors for shoulder injury are prominent among professional and elite male handball players. The primary factors for eventual shoulder injury are shoulder muscle imbalances, range of motion (ROM) discrepancies, glenohumeral internal rotation deficit (GIRD), and scapular dyskinesis. Also, in one study authors specified player position as a potential risk factor.